Stimulation of unconventional hydrocarbon reservoirs - Szabó, Dávid; Pinka, Ján; Stoličný, Eduard (My University, 2014)
In the »new age« oil and gas industry came more and more into focus term of unconventional hydrocarbons. Gained experience and success in the United States tight gas sand reservoirs Piceance, Anadarko, Greater Green, Lobo fields confirmed the hidden potential of unconventional hydrocarbon resources. In some production and development areas called coal bed seam, shale gas and tight sand reservoirs without intensifying operations isn't possible to produce commercial gas volumes. Used practises and gained large experiences in the crude oil fields are commonly used in the shale and tight gas fields across the United States. Application of these technologies of stimulation methods like fracturing in Europe is at the very beginning. Pioneer investors are waiting in all Europe for the well testing results from the first dozen fractured shale gas and tight sand reservoirs. Test results could have significant influence on the future planned massive drilling campaign of exploration of the unconventional hydrocarbon resources.
AGH Drilling, Oil, Gas
Keywords: Tight gas sand; shale gas; coal bed seam unconventional; intensification; fracturing; propant; mesh; Darcy's law